2019
DOI: 10.1111/age.12771
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of de‐domestication in autochthonous pig breeds and of domestication in wild boar populations from MC1R and NR6A1 allele distribution

Abstract: Autochthonous pig breeds are usually reared in extensive or semi-extensive production systems that might facilitate contact with wild boars and, thus, reciprocal genetic exchanges. In this study, we analysed variants in the melanocortin 1 receptor (MC1R) gene (which cause different coat colour phenotypes) and in the nuclear receptor subfamily 6 group A member 1 (NR6A1) gene (associated with increased vertebral number) in 712 pigs of 12 local pig breeds raised in Italy (Apulo-Calabrese, Casertana, Cinta Senese,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Throughout its history, the wild boar has been strongly influenced by human practices such as hunting, pig domestication, and animal translocation (Larson et al, 2005;Scandura, Iacolina, & Apollonio, 2011). Previous studies revealed the complex genetic structure of wild boar populations in Eurasia, including multiple domestication events and gene flow between wild boar and domestic pig breeds (Iacolina et al, 2016;Larson et al, 2005;Ramíres et al, 2009;Ribani et al, 2019;Šprem et al, 2014). Previous studies revealed the complex genetic structure of wild boar populations in Eurasia, including multiple domestication events and gene flow between wild boar and domestic pig breeds (Iacolina et al, 2016;Larson et al, 2005;Ramíres et al, 2009;Ribani et al, 2019;Šprem et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout its history, the wild boar has been strongly influenced by human practices such as hunting, pig domestication, and animal translocation (Larson et al, 2005;Scandura, Iacolina, & Apollonio, 2011). Previous studies revealed the complex genetic structure of wild boar populations in Eurasia, including multiple domestication events and gene flow between wild boar and domestic pig breeds (Iacolina et al, 2016;Larson et al, 2005;Ramíres et al, 2009;Ribani et al, 2019;Šprem et al, 2014). Previous studies revealed the complex genetic structure of wild boar populations in Eurasia, including multiple domestication events and gene flow between wild boar and domestic pig breeds (Iacolina et al, 2016;Larson et al, 2005;Ramíres et al, 2009;Ribani et al, 2019;Šprem et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, analysis of the changes in the geographical range of S. scrofa could aid our understanding of not only the global patterns of evolution and ecosystem change (Anijalg et al, 2018). Previous studies revealed the complex genetic structure of wild boar populations in Eurasia, including multiple domestication events and gene flow between wild boar and domestic pig breeds (Iacolina et al, 2016;Larson et al, 2005;Ramíres et al, 2009;Ribani et al, 2019;Šprem et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…( 14,16,28 but see also 34,38,39 www.nature.com/scientificreports www.nature.com/scientificreports/ All reference pigs showed the domestic allele (T) at the NR6A1 gene (Table 5), except two individuals from family-owned farms that were pig × wild boar hybrids (T/C). Of these, one had already been identified by STRs.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing of MC1R on chromosome 6 in S. scrofa revealed a series of single-base substitutions corresponding to different E alleles with phenotypic effects 21,22 . The wild type allele E + (or 0101, sensu 13 ), determining a typical brownish-grey coat colour, is private to the European and Asian wild boar populations, and to the Hungarian Mangalica swine breed 13,14 . The variants E D2 (0301), E P1/2/3 (0501/0502/0503) and the recessive allele e (0401) are of domestic European origin, and determine different coat colours, from black to spotted, white, and reddish.…”
mentioning
confidence: 99%
“…The high frequency of the heterozygous C/T genotype in Turopolje, a domestic pig breed from Croatia, is in accordance with a very recent paper of the research group of Fontanesi. By genotyping 47 Turopolje individuals, the frequency of the T and the C allele were reported to be 0.57 and 0.43, respectively 19 .…”
Section: Resultsmentioning
confidence: 99%